Microgrid Communication Network Optimization During Disaster Relief: A Connectivity Rank Index Based Approach - Tian, Hengrui; Joshi, Aditya; Chow, Mo-Yuen; Zhou, Jin; Chen, Guanrong (IEEE International Conference on Industrial Technology (Online), 2025)
After disasters, power is urgently needed especially for medical facilities. However, power systems as well as communication systems could be severely damaged during disasters. Thus, power restoration with limited communication resources is a critical task during disaster relief. In this paper, a novel strategy is proposed for communication network optimization in microgrid energy management system (EMS). It applies connectivity rank index (CRI) to measure the importance of edges. The proposed strategy aims to achieve fast response of energy management using least communication resources in disaster relief processes. It relies on CRI to identify redundant edges and removes them from the original network one after another iteratively. Numerical simulations were performed on a 14-node system. Results show that the convergence speed is increased by 79.12% and the communication efficiency is increased by 14.98%, demonstrating the effectiveness of the proposed strategy.